A Chromosome 4q25 Variant is Associated with Atrial Fibrillation Recurrence After Catheter Ablation: A Systematic Review and Meta-Analysis - Rattanawong, Pattara (J Atr Fibrillation, 2018)
BACKGROUND: Recent studies suggested that variants on chromosome loci 4q25, 1q21, and 16q22 were associated with atrial fibrillation recurrence after catheter ablation. In this study, we performed a systematic review and meta-analysis to explore the association between variants on chromosome loci 4q25, 1q21, and 16q22 and atrial fibrillation recurrence after catheter ablation METHODS: We comprehensively searched the databases of MEDLINE and EMBASE from inception to January 2017. Included studies were published prospective or retrospective cohort and case control studies that compared the risk of atrial fibrillation recurrence after catheter ablation in AF patients with chromosome 4q25, 1q21, and 16q22 variants versus no variants. Single-nucleotide polymorphism rs1906617, rs2106261, rs7193343, rs2200733, rs10033464, rs13376333, and rs6843082 were included in this analysis. Data from each study were combined using the random-effects, generic inverse variance method of DerSimonian and Laird to calculate the risk ratios and 95% confidence intervals RESULTS: Seven studies from January 2010 to June 2017 involving 3,322 atrial fibrillation patients were included in this meta-analysis. According to the pooled analysis, there was a strong independent association between chromosome 4q25 variant (rs2200733) and the risk of atrial fibrillation recurrence after catheter ablation (risk ratio 1.45 [95% confidence interval 1.15-1.83], P = 0.002). No association was found in other variants CONCLUSION: Our meta-analysis demonstrates a statistically significant increased risk of atrial fibrillation recurrence after catheter ablation in 4q25 variant (only in rs2200733) but not in 1q21 or 16q22 variants.